Developing an intervention to improve early infant HIV diagnosis service uptake among postpartum women in Malawi's primary healthcare using a co-designing approach with stakeholders. - Leticia Chimwemwe Suwedi-Kapesa; Augustine Talumba Choko; Alinane Linda Nyondo-Mipando; Jenifer Hezekiah Zimba; Edda Lipipa; Dorcus Nothale; Afunawo Mdala Maulukira; Joe Nkhonjera; Melody Sakala; Nicola Desmond; Angela Obasi (PLOS Global Public Health)
Low health service use by women and infants after birth limits early infant HIV diagnosis (EID). From August 2021 to December 2022, we collaborated with 44 healthcare workers (HCW), service users, and non-governmental organisation stakeholders from seven public facilities and five non-governmental organisations in Blantyre, building on a previous study. We analysed context-specific problems in EID services and co-designed a context-appropriate enhanced health system intervention to improve the uptake of six weeks' EID services in primary health facilities in Blantyre, Malawi, using qualitative methods and co-designing workshops. The Behaviour Change Wheel, Theoretical Domain Framework and Consolidated Framework for sustainability constructs in healthcare guided the workshops. Reflexive thematic analysis of the data showed that stakeholders found that EID services were sub-optimal and identified challenges to service provision in 5 key areas: (1) client identification, (2) context-appropriate client-centred service integration, (3) HCW coordination and accountability, (4) HCW capacity building for optimal service delivery, and (5) intervention sustainability. Specifically, client and HCW stigma perceptions, referral gaps, resource challenges, HCW lack of time and poor documentation affected client identification; HCW clustered work shifts to extend off-duty periods, failure to synchronise client appointments, and lack of resources were barriers to client-centred integrated services; dysfunctional teams, minimal supervision and misconduct among HCW impacted coordination and accountability; and lack of information sharing and limited training reduced HCW capacity for service delivery. Context-appropriate stakeholder informed co-design initiatives to address identified challenges included: clients' unique identifiers, booking systems, strengthening leadership, data validation, care pathways, and facility-based training. We recommend evaluating these initiatives in low resource settings as they have potential to address the identified EID service implementation gaps and significantly improve the EID of HIV in contexts of greatest need.